Bjorken Flow Revisited: Analytic and Numerical Solutions in Flat Space-Time Coordinates (Communications in Computational Physics, 2023)
In this work we provide analytic and numerical solutions for the Bjorkenflow, a standard benchmark in relativistic hydrodynamics providing a simple modelfor the bulk evolution of matter created in collisions between heavy nuclei.We consider relativistic gases of both massive and massless particles, working ina (2+1) and (3+1) Minkowski space-time coordinate system. The numerical resultsfrom a recently developed lattice kinetic scheme show excellent agreement with theanalytic solutions.